The Dynamics of Lawang Sewu: As a Railway Museum 2011-2023 - Safitri, Anis; Wijayati, Putri Agus (Universitas Negeri Semarang, 2024)
This study aims to examine the efforts to revitalize the function of Lawang Sewu, transforming it from a building known for its mystical image into a museum utilizing digital technology in the modern era. One of the main focuses of this research is the importance of preserving heritage buildings to raise public awareness, unlock economic potential through tourism, and serve as a symbol of local identity. The study employs a historical method, beginning with data collection from primary sources, both written and oral. Written primary sources were found in the Suara Merdeka newspaper and official decrees issued in the same year. Oral primary sources were gathered through interviews with six museum management staff and ten visitors to the Lawang Sewu Museum. The findings reveal the success of digital technology implemented by PT. KAI and the museum management. Moreover, the building has successfully adapted to the challenges of modern times through physical restoration, repurposing, and rebranding, effectively shedding its mystical image. Restoration efforts involved physical repairs, the addition of accessibility facilities, and the inclusion of artifacts relevant to the history of Indonesian railways. Modern technological applications, such as video mapping, immersive exhibitions, and virtual tours, have significantly enhanced the museum's appeal, particularly for the younger generation accustomed to digital technology.